GAGASAN PEMIKIRAN HUMANISTIK DALAM PENDIDIKAN (Perbandingan Pemikiran Naquib al-Attas Dengan Paulo Freire) - Khusnul Mualim (Universitas Muhammadiyah Ponorogo, 2017)
Humanistic thought in education has always been interesting to be discussed. As between two figures who discuss humanistic education is Naquib al-Attas and Paulo Freire. The purpose of doing research is the study of humanistic thought from the second related about: (1) the meaning of humanistic psychology in education; (2) the thought of humanistic Naquib al-Attas and Paulo Freire; (3) the Humanistic Education in Islam; and (4) Seeking similarities and differences of humanistic thought both figures in the context of Islamic education. A research method in this research is qualitative research. The collection of data in this study using the method of documentation. Data analysis was done by providing a hidden meaning to the data that was successfully collected based on primary data. The technique of the validity of the data by triangulation. Based on the results of research conducted, the following conclusions were obtained: (1) the Humanistic in Islamic education is a process of education that paying more attention to aspects of human potential as being given a chance by the Almighty God to develop the potential in themselves; (2) the MenurutNaquib al-Attas, humanistic religious concept puts human being having regard to responsibility. Meanwhile, according to Paulo Freire, humanistic is the concept of giving freedom to the individual human being; (3) the Humanistic Education in Islam is an effort of the embodiment or manifestation of the self in the world of Islamic education; (4) the equation of the theory of both figures are located on its object, the man. While the difference is based on human concepts, goals, and values.